Oxygen Defect-Mediated Magnetism in Fe-C Codoped TiO2 - Zhaorui Zou; Zhongpo Zhou; Haiying Wang; Meng Du (Advances in Materials Science and Engineering)
The magnetic properties of the C doped and C-Fe codoped TiO2 films fabricated by sol-gel and spin coating have been investigated combining experiments and first-principles calculations. All the samples exhibit the anatase crystal phase and the room temperature ferromagnetism. The values of the saturation magnetizations are in the order of Fe-C codoped TiO2 > Fe-C codoped TiO2 (annealed in O2) > C doped TiO2 > C doped TiO2 (annealed in O2). The calculated net moment values are in the order of Fe-C codoped TiO2 > C doped TiO2 with oxygen vacancies existing, in accord with the experimental results. The hybridization of Fe 3d, C 2p, and O 2p (nearest to the Fe defect) led to the spin split of Fe 3d, C 2p, and O 2p which contributed to the ferromagnetism.